On the analysis of magnetohydrodynamics and magnetic field-dependent viscosity effects on thermogravitational convection of hybrid nanofluid in an enclosure with curved walls (vol 33, 102010, 2021) - Pandit, Swapan K.; Goswami, Krishno D.; Chattopadhyay, Anirban; Öztop, Hakan Fehmi (Aip Publishing, 2021)
[Abstract Not Available]